Moderate Changes in the Circadian System of Alzheimer's Disease Patients Detected in Their Home Environment - Weissová, Kamila; Bartoš, Aleš; Sládek, Martin; Nováková, Marta; Sumová, Alena (PloS one, 2016)
Alzheimer's disease (AD) is a neurodegenerative disease often accompanied with disruption of sleep-wake cycle. The sleep-wake cycle is controlled by mechanisms involving internal timekeeping (circadian) regulation. The aim of our present pilot study was to assess the circadian system in patients with mild form of AD in their home environment. In the study, 13 elderly AD patients and 13 age-matched healthy control subjects (the patient's spouses) were enrolled. Sleep was recorded for 21 days by sleep diaries in all participants and checked by actigraphy in 4 of the AD patient/control couples. The samples of saliva and buccal mucosa were collected every 4 hours during the same 24 h-interval to detect melatonin and clock gene (PER1 and BMAL1) mRNA levels, respectively. The AD patients exhibited significantly longer inactivity interval during the 24 h and significantly higher number of daytime naps than controls. Daily profiles of melatonin levels exhibited circadian rhythms in both groups. Compared with controls, decline in amplitude of the melatonin rhythm in AD patients was not significant, however, in AD patients more melatonin profiles were dampened or had atypical waveforms. The clock genes PER1 and BMAL1 were expressed rhythmically with high amplitudes in both groups and no significant differences in phases between both groups were detected. Our results suggest moderate differences in functional state of the circadian system in patients with mild form of AD compared with healthy controls which are present in conditions of their home dwelling.
Keywords: cirkadiánní rytmus; Humans; Sleep Disorders, Intrinsic; Case-Control Studies; messenger RNA; regulace genové exprese; studie případů a kontrol; melatonin; aktigrafie; životní prostředí; Environment; Actigraphy; Aged; Female; ARNTL Transcription Factors; Housing; transkripční faktory ARNTL; senioři; lidé; Alzheimer Disease; Alzheimerova nemoc; Medical Records; Saliva; poruchy spánku z vnitřních příčin; Circadian Rhythm; chorobopisy; bydlení; ústní sliznice; RNA, Messenger; ženské pohlaví; Gene Expression Regulation; Male; sliny; Aged, 80 and over; senioři nad 80 let; Mouth Mucosa; mužské pohlaví; cirkadiánní proteiny Period; Period Circadian Proteins; Melatonin